2019
DOI: 10.1186/s40663-019-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

A constructive review of the State Forest Inventory in the Russian Federation

Abstract: The State Forest Inventory (SFI) in the Russian Federation is a relatively new project that is little known in the English-language scientific literature. Following the stipulations of the Forest Act of 2006, the first SFI sample plots in this vast territory were established in 2007. The 34 Russian forest regions were the basic geographical units for all statistical estimates and served as a first-level stratification, while a second level was based on old inventory data and remotely sensed data. The sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Once finalized, the NFI will be verified before adoption as the official source of information to the SFR and national reporting. The NFI has received some criticism 13 because of the relatively sparse sampling employed and the stratification method used, which is partially based on outdated FIP data.…”
Section: Mainmentioning
confidence: 99%
“…Once finalized, the NFI will be verified before adoption as the official source of information to the SFR and national reporting. The NFI has received some criticism 13 because of the relatively sparse sampling employed and the stratification method used, which is partially based on outdated FIP data.…”
Section: Mainmentioning
confidence: 99%
“…According to the FRA report for Russia (FRA national report: http://www.fao. org/3/cb0053en/cb0053en.pdf, last access: 31 May 2021), almost 80 % of the total land area on which forests are located is in "hard-to-reach" places beyond the 60th parallel (Alekseev et al, 2019). Since most of the deforestation caused by wildfires takes place in those regions (Curtis et al, 2018), inventories could present large underestimations of the reported losses.…”
Section: Reasons For Disparities In Tree Cover Areas and Trendsmentioning
confidence: 99%
“…Including the soil moisture stress effect (γ SM ) based on ERA-Interim soil moisture data would lead to a further decrease of the order of 10 % (Table S5). Disparities among the inventories are primarily attributed to differences in meteorological fields and emission potential distributions (Arneth et al, 2011), with additional possible contributions of differences in the canopy environment models and in the LAI datasets.…”
Section: Global and Total Emissions Distributions And Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of observational infrastructures are national forest inventories, field experiments and long-term observational studies. The objective of a national forest inventory is to prepare reports about the state of the forest resource at a given time and within a specific geographical context (Alekseev et al, 2019;Zeng et al, 2015). Field experiments are established to evaluate ecosystem response to specific treatments.…”
Section: Introductionmentioning
confidence: 99%